Economic Impact of Coal Mining Investment in East Kalimantan: An Input Output Approach - Surbakti, Sinarta Putra P.; Nurhidayati (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2025)
Research Originality — This research distinguishes itself from existing literature by offering a novel empirical assessment of the economic impact of coal mining investment in East Kalimantan, the province with Indonesia’s largest coal reserve and major contributor to national investment. It further contributes originality by employing an updated 2022 Input-Output Table to estimate sectoral output, employment, and fiscal contributions. Research Objective — This research aims to measure the impact of coal mining investment on the economy of East Kalimantan in 2022. The economic impact will be examined through output, employment, and the potential state revenue from taxation and non-taxation. Research Methods — The study employs the input-output table (IO Table) analysis technique for East Kalimantan in 2016, updated using the RAS approach to create the IO Table for the year 2022. The economic shock utilized is the realization of investments in coal and lignite mining from foreign direct investment (FDI) and domestic investment in East Kalimantan. Empirical Results — The findings reveal that coal and lignite mining investments in 2022 could increase output by Rp20 trillion, employ 7,323 individuals, and potentially generate state revenues of Rp619,18 billion from the taxation sector and Rp960,64 billion from the non-taxation sector. The research also indicates that the mining and quarrying sector, encompassing coal and lignite mining, effectively stimulates downstream industries, suggesting that downstream output from the mining and quarrying sector can provide added value to the economy. Implications — The study demonstrates that coal mining investment generates significant multiplier effects on output, employment, and fiscal revenue. Accordingly, effective policies to enhance investment, encourage industrialization, and ensure sustainable resource use are essential for translating these impacts into stronger regional economic growth and long-term development in East Kalimantan.